A Bibliography of Indonesian literature in juornals: drama, prose, poetry = Bibliografi karya sastra indonesia dalam majalah drama, prosa, puisi - Ernst Ulrich Kratz (Gajah Mada University Press, 1988)
oen, c.1-7/stc13,c.8